Molecular and Biochemical Characterization of VEB-1, a Novel Class A Extended-Spectrum β-Lactamase Encoded by an Escherichia coli Integron Gene - Poirel, Laurent (American Society for Microbiology, 1999)
A clinical isolate, Escherichia coli MG-1, isolated from a 4-month-old Vietnamese orphan child, produced a β-lactamase conferring resistance to extended-spectrum cephalosporins and aztreonam. In a disk diffusion test, a typical synergistic effect between ceftazidime or aztreonam and clavulanic acid was observed along with an unusual synergy between cefoxitin and cefuroxime. The gene for VEB-1 (Vietnamese extended-spectrum β-lactamase) was cloned and expressed in E. coli JM109. The recombinant plasmid pRLT1 produced a β-lactamase with a pI of 5.35 and conferred high-level resistance to extended-spectrum (or oxyimino) cephalosporins and to aztreonam. V(max) values for extended-spectrum cephalosporins were uncommonly high, while the affinity of the enzyme for ceftazidime and aztreonam was relatively low. bla(VEB-1) showed significant homology at the DNA level with only bla(PER-1) and bla(PER-2). Analysis of the deduced protein sequence showed that VEB-1 is a class A penicillinase having very low levels of homology with any other known β-lactamases. The highest percentage of amino acid identity was 38% with PER-1 or PER-2, two uncommon class A extended-spectrum enzymes. Exploration of the genetic environment of bla(VEB-1) revealed the presence of gene cassette features, i.e., (i) a 59-base element associated with bla(VEB-1); (ii) a second 59-base element just upstream of bla(VEB-1), likely belonging to the aacA1-orfG gene cassette; (iii) two core sites (GTTRRRY) on both sides of bla(VEB-1); and (iv) a second antibiotic resistance gene 3′ of bla(VEB-1), aadB. bla(VEB-1) may therefore be the first class A extended-spectrum β-lactamase that is part of a gene cassette, which itself is likely to be located on a class 1 integron, as sulfamide resistance may indicate. Furthermore, bla(VEB-1) is encoded on a large (>100-kb) transferable plasmid found in a Klebsiella pneumoniae MG-2 isolated at the same time from the same patient, indicating a horizontal gene transfer.